CD4+T and CD8+T cells profile in lung inflammation and fibrosis: targets and potential therapeutic drugs - Sun, Xiaobo; Zhang, Xinwen; He, Yuhan; Du, Xueting; Cai, Qian; Liu, Zhihong (Frontiers in Immunology, 2025)
Pulmonary fibrosis is an interstitial lung disease characterized by chronic progressive fibrosis. It is associated with fibrocyte proliferation and collagen deposition, leading to severe, irreversible lung function decline. Despite extensive research, the diagnosis and treatment of pulmonary fibrosis are complicated and have no effective treatment. During the formation of pulmonary fibrosis, immune dysregulation by inflammatory cell infiltration is the key driver of pulmonary fibrosis. Recently, single-cell sequencing analysis of silicosis mice showed that various cells in the alveolar immune microenvironment are involved in forming pulmonary fibrosis, such as macrophages, fibroblasts, epithelial cells, etc. Among them, T cell subpopulations in silicosis mice were significantly activated, indicating that T lymphocyte subsets play an essential role in the process of pulmonary fibrosis. More and more pulmonary clinical studies show that T lymphocytes in the lung immune microenvironment play an important and multifaceted role. This article summarizes the role of CD4+T cells and CD8+T cells in pulmonary fibrosis. This article provides some new insight into the potential therapy target that can delay the process of pulmonary fibrosis by regulating the proportions of different subpopulations of T lymphocytes and some related signaling pathways.